The Impact of Access to Capital and Financial Technology on the Business Performance of SME in Sidoarjo, Indonesia - Unusida, Alifia Sabina Parahita; Fahriani, Dian; Muzakki, Kafidin; Wicaksono, Achmad (Manunggal Halim Jaya, 2025)
This study examines the impact of access to capital and financial technology on the business performance of micro, small, and medium enterprises (SME) in Sidoarjo, Indonesia. Adopting a quantitative approach, the research surveyed 100 SME owners and employed multiple linear regression analysis to explore the relationship between these variables. The findings reveal that access to capital and financial technology positively and significantly impact SME performance. The study highlights the crucial role of digital financial services in enhancing financial inclusion and suggests that improved access to funding enhances operational capacity and fosters growth. These insights aim to guide government and institutional policies that bolster SME resilience and development in the digital age.